High availability web server (clustering) / Muhammad Akhtar Md Yusoff - Md Yusoff, Muhammad Akhtar (2015)
Cluster is very good in management database system. This is because it can make reduce downtime and make system database more effusions. In performance database is automatically and transparently partitioned across low cost commodity nodes, allowing scale-out of read and write queries, without requiring changes to the application. Mysql function multi-master replication its means each data node can accept write operation. Coupled with auto sharing, this gives very high write scalability. For the real time responsiveness, low latency with in memory table and indexes, asynchronous check pointing to disk and binding of treads to CPUs. Implementation Mysql cluster schemes can improve system performance better than using a single database. Implementation Mysql cluster with schemes can provide availability system is maintained and scalability enough to be able to continue to serve each request of the user.This document contains information of the requirement analysis, design, implementation, testing of the container booking and management system. The project finished and web server release successfully, planning for Reliability and High Availability from down time.